Influencers of Inflation in Ghana - Acquah-Sam, Emmanuel (European Scientific Journal, ESJ, 2017)
The effects of inflation on the economic life of the citizenry of a country and the theoretical causes have led to numerous researches in the area. Annual inflation rates in Ghana since 1990 show a fluctuating trend depicting how unsuccessful various governments and policy-makers have battled with changes in the general price level. The theoretical and empirical literature on inflation seem to suggest that the causes of inflation are multifaceted, and time specific, as well as dependent on the level of development of a country. This paper attempts to explore some of major triggers of inflation Ghana for decision-making and implementation as well as adding to existing researches in the area. It uses multiple linear regression analysis based on structural equation modelling through path analysis. It concludes that interest rate, proxied by Treasury bill rates, is the only major variable that has a positive and significant effect on inflation in Ghana with regard to the time period studied. Factors such as GDP growth, market capitalisation, gross fixed investment, and foreign direct investments proved insignificant in influencing inflation in Ghana. This study lends support to the fact that inflation reacts positively to changes in interest rates, therefore, governments and policy-makers must consider it critical when pursuing propoor growth policies.